2014
DOI: 10.7852/ijie.2014.28.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Insect Pathogen Serratia marcescens in Protaetia brevitarsis seulensis (Kolbe) from Korea

Abstract: Protaetia brevitarsis seulensis (Kolbe) is widely used in Korea, as a protein-rich, alternate, functional food with pharmacological benefits. In addition to anti-oxidant properties, the larvae of P. b. seulensis also show positive effects against hepatic disorder and diabetes; therefore, P. b. seulensis larvae are being reared on a large scale in Korea. We evaluated reared larvae of P. b. seulensis from Gyeong-gi in Korea. Using 16SrRNA PCR, electro-microscopy, and bioassay techniques, we found that the larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…seulensis larvae via hemolymph injection of S. marcescens (Kwak et al 2014), but showed 0% mortality when 3 We observed mortality after 4 wk when insect sawdust was treated with Sm together with Bt and Pp, which are known to its mortality rate after 4 wk was 95.23%, which was 42.85% higher than the Pp treatment alone. Since mortality is maximal when P. popilliae and S. marcescens are detected together in a breeding environment or in sawdust, the results of this study can be utilized in the prevention and diagnosis of such cases.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…seulensis larvae via hemolymph injection of S. marcescens (Kwak et al 2014), but showed 0% mortality when 3 We observed mortality after 4 wk when insect sawdust was treated with Sm together with Bt and Pp, which are known to its mortality rate after 4 wk was 95.23%, which was 42.85% higher than the Pp treatment alone. Since mortality is maximal when P. popilliae and S. marcescens are detected together in a breeding environment or in sawdust, the results of this study can be utilized in the prevention and diagnosis of such cases.…”
Section: Resultsmentioning
confidence: 78%
“…Bombyx mori (Lepidoptera: Bombycidae), P. b. seulensis (Coleoptera: Cetoniidae), and Rhagoletis pomonella (Diptera: Tephritidae) (Ishii et al 2014;Kwak et al 2014;Lauzon C. R. 2003). Moreover, S. marcescens is also considered to be an opportunistic pathogen and can cause antibioticresistant hospital-acquired infections (Murdoch et al 2011).…”
Section: S Marcescens Is Lethal To Many Kinds Of Insects Includingmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that this isolate is highly virulent to the beetle larvae and inhibits the insect egg hatching in laboratory experimental conditions. Larval stages are the longest of the insect life cycle, where the insect feeds on various sources of decaying cellulose, including roots of grass and weed, rice straw and Oakwood [13]. The subterranean habitats of the white grubs, make them difficult to control since applied insecticides have to move into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…This species is widely distributed in Korea, Japan, China, Taiwan and some parts of Europe [11,12]. Its life cycle comprises the embryo, larva, pupa, and imago stages, of which the larval stage is the longest and is the stage when the insect feeds and stores energy for the rest of the life cycle [13]. Depending on habitat conditions, adults can be observed in Korea from May to October with greatest abundance in July.…”
Section: Introductionmentioning
confidence: 99%